Merits of expanding the Utstein case definition for out of hospital cardiac arrest. (January 2021) - Shin, Jenny; Chocron, Richard; Rea, Thomas; Kudenchuk, Peter; McNally, Bryan; Eisenberg, Mickey
Abstract: Background: The Utstein population is defined by non-traumatic, bystander-witnessed out-of-hospital cardiac arrest (OHCA) presenting with ventricular fibrillation (VF). It is used to compare resuscitation performance across emergency medical services (EMS) systems. We hypothesized a system-specific survival correlation between the current Utstein population and other VF populations defined by unwitnessed VF OHCA and VF OHCA after EMS arrival (EMS-witnessed). Expanding performance metrics to this more comprehensive population would make the Utstein definition more representative of the actual community burden and response to VF OHCA. Methods: We performed a cohort investigation of all non-traumatic, VF OHCA in the Cardiac Arrest Registry to Enhance Survival from 1/1/2013-12/31/2018 among EMS agencies that treated > = 100 VF OHCA. We evaluated sample size and survival with the addition of the new VF populations. We used Pearson coefficient to assess whether there was a correlation of agency-specific survival outcomes between the current Utstein population and unwitnessed and EMS-witnessed VF OHCA. Results: A total of 107 EMS agencies treated 38, 836 VF arrests: 22, 918 current Utstein, 11, 297 unwitnessed VF, and 4621 EMS-witnessed VF OHCA. Overall, survival was 29.8% (11, 567/38, 836): 33.9% (7774/22, 918) among current Utstein, 17.2% (1942/11, 297) among unwitnessed VF, and 40.1% (1851/4621) among EMS-witnessed VF. For agency-specific survival outcome, the Pearson correlation was 0.52 between the current Utstein population versus combined unwitnessed and EMS-witnessed groups. For survival with Cerebral Performance Category 1–2, the Pearson correlation was 0.61. Conclusion: Expanding the Utstein population to include unwitnessed and EMS-witnessed VF OHCA achieves a simpler, more inclusive case definition that minimizes variability in case determination and increases the number of survivors and eligible population by ∼50%, while still achieving a distinguishing metric of system-specific performance.